Critical topics in Bangladesh’s and Nigeria’s food system related policies: An exploratory policy review - Bakker, S.; Beune, R.; Herens, M.; Pittore, K. (Wageningen Centre for Development Innovation, 2021)
Nigeria and Bangladesh from a food systems perspective. Its aim is to identify the most important policy topics identified in current p[policies related to nutrition and healthier diets at the national level. The key questions addressed were: 1) What are the critical topics from a food system’s [perspective, highlighted in national policies, to be addressed in order to improve food system’s outcomes and healthier diets? 2) How do food system related topics relate to the current agendas of existing platform initiatives? The analysis serves to demonstrate which domains of the food system have the emphasis of policy in both countries. For Bangladesh, the study concluded that the documents tend to focus on the food production side as well as the consumer side, alongside market connectivity, improving market infrastructure and reducing price volatility, while the transportation, shortage, processing, and retail functions of a food value chain tend to receive less attention. For Nigeria, the study concluded that there is a clear production issue: insufficient food is produced for national consumption and high postharvest losses are high. This in combination with a growing population and rapid urbanization leads to inequalities between rural and urban areas, between the North and South of the country and between women and men, and the risk of conflict situations put the food system under pressure. The triple burden of nutrition is well recognised, as well as food safety issues. The findings show that in Nigeria the emphasis is on interventions at storage, distribution, processing, retail and marketing level and with interventions directed at the consumer. Finally, the results are compared to the results of the A4NH P4HD Platforms Identification study from 2017, to see how the goals of the platforms identified align with the most important themes at national level. The findings of this study in relation to the Platform identification study indicate that platforms may be more focused on the day-to-day practice and build on historically grown consensus what to address, and not necessarily adopt forward looking current policies.